Flax xylem as composite material reinforcement: Microstructure and mechanical properties. (October 2021) - Nuez, Lucile; Magueresse, Anthony; Lu, Pin; Day, Arnaud; Boursat, Thomas; D'Arras, Pierre; Perré, Patrick; Bourmaud, Alain; Baley, Christophe
Highlights: Deeper insight in flax shives was sought by analysing the xylem tissue of flax. The microstructure of flax xylem was detailed by nanotomography and image analysis. Indentation modulus of secondary xylem cell walls was measured by AFM Peak Force. The tensile modulus of biocomposites was estimated by a micromechanical model. Abstract: Flax shives have been proven to be relevant injection-moulded reinforcement materials with a stiffness that reaches 90% of that obtained with cut flax fibres. Nevertheless, little is known of the reinforcing mechanisms of this material. In this study, deeper insight is sought on the mechanical properties of flax shives, which originate mainly from the xylem tissue of the flax stems. The microstructure of flax xylem is investigated by nanotomography and image analysis as a function of stem height, combined with AFM measurements of the cell walls in Peak Force Quantitative Nano Mechanical indentation mode (20–22 GPa were measured for the S2 layer). The bending stiffness of peeled flax stems was furthermore investigated, and finally, an estimation of the flax shive particle stiffness was carried out and tested with a micromechanical approach in order to evaluate their reinforcing potential in injection-moulded composites.